Analisis Strukturalisme Cerpen “Laysa Lahā Makān Fī Al-Jannah” Karya Nawal El-Saadawi dengan Pendekatan Robert Stanton - Rizalman, Mhd; Nurhaliza, Yesi; Riza, Yulfira; Fitria Utami, sinta; Fitria Utami, Shinta (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
This study analyzes the short story "Laysa Lahā Makān Fī Al-Jannah" by Nawal El-Saadawi with the aim of exploring intrinsic elements using Robert Stanton's structuralism approach. This research applies a qualitative approach that is descriptive. The data source is taken from the anthology of the short story "Adab Am Qillat Adab" by Nawal El-Saadawi. The data in this study was collected using library techniques, reading techniques and note-taking techniques. The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawn. The results obtained from this study found 3 constructive elements in this short story, namely: 1). The theme contained in the short story Laysa Lahā Makān Fī Al-Jannah, namely the misery experienced by Zainab where her mother, father, and husband always committed acts of violence against her. 2). The facts of the story; a) using a reverse groove; b) figures; Zainab, Zainab's husband, Zainab's mother, and Zainab's father. c) The setting of the place (in heaven and in the grave); The time setting (before dawn and night), and the social setting is patriarchal culture. 3). Literary facilities; a) The title "Laysa Lahā Makān Fī Al-Jannah". b) using a third-person point of view. c) The language style is influenced by the Ammiyah language of Egypt. The tone that often appears is a sad tone. d) The symbol that appears in this short story is a depiction of Zainab's physical characteristics. e) Lastly, dramatic irony is found. This study contributes to the broader understanding of feminist literature in Middle Eastern context by highlighting the systemic oppression of women as potrayed in El-Saadawi’s work.